Emotion, deliberation, and the skill model of virtuous agency. (1st May 2018) - Kurth, Charlie
Abstract : A recent skeptical challenge denies deliberation is essential to virtuous agency: what looks like genuine deliberation is just a post hoc rationalization of a decision already made by automatic mechanisms. Julia Annas's account of virtue seems well‐equipped to respond: by modeling virtue on skills, she can agree that virtuous actions are deliberation‐free while insisting that their development requires significant thought. But Annas's proposal is flawed: it over‐intellectualizes deliberation's developmental role and under‐intellectualizes its significance once virtue is acquired. Doing better requires paying attention to a distinctive form of anxiety—one that functions to engage deliberation in the face of decisions that automatic mechanisms alone cannot resolve.